The impact of Danmu on Consumer Purchase Intention in Live-streaming E-commerce in China - Gong, Xuewen; Stříteský, Václav; Fortelný, Martin; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This paper discusses the increasing popularity of live streaming e-commerce in China, and how the emergence of Danmu is changing the way consumers interact with the anchor and with each other during live streams. The purpose of study is to evaluate how Danmu affects consumer purchase intention in the live room. The study employs the Stimuli-Organism-Response theory and the Technology Acceptance Model to explore the relationship between danmu characteristics and consumer behavior. The study collected data through questionnaire surveys and analyzed 405 valid questionnaires using SPSS and AMOS. I found that the quality of danmu and positive emotional danmu have a positive impact on consumer purchase intention and perceived value, and a negative impact on perceived risk. Perceived value and perceived risk play mediating roles in the relationship between danmu characteristics and consumer purchase intention. Consumer shopping orientation has a significant moderating effect on the relationship between perceived risk and consumer purchase intention. The study provides practical recommendations for companies, emphasizing the importance of consumer interaction through Danmu, adjusting Danmu topics and interaction methods based on consumer shopping tendencies, and developing information filtering and blocking functions to improve the consumer shopping experience. The study highlights the impact and mechanism of positive emotional danmu information characteristics on consumer behavior in live streaming marketing, and contributes to the understanding of the role of live streaming e-commerce in the Chinese economy.
Vedoucí práce: Václav Stříteský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses